Benefits of ultra-fast-track anesthesia for children with congenital heart disease undergoing cardiac surgery - Jing Xu; Guanghua Zhou; Yanpei Li; Na Li (BMC, 2019)
Abstract Background To compare the outcomes of ultra-fast-track anesthesia (UFTA) and conventional anesthesia in cardiac surgery for children with congenital heart disease (CHD) and low birth weight. Methods One hundred and ninety-four CHD children, aged 6 months to 2 years, weighting 5 to 10 kg, were selected for this study. The 94 boys and 100 girls with the American Society of Anesthesiologists (ASA) physical status III and IV were randomly divided into two groups each consisting of 97 patients, and were subjected to ultra-fast-track and conventional anesthesia for cardiac surgery. For children in UFTA group, sevoflurane was stopped when cardiopulmonary bypass (CPB) started and cis-atracurium was stopped at the beginning of rewarming, and remifentanil (0.3 μg/kg/mim) was then infused. Propofol and remifentanil were discontinued at skin closure. 10 min after surgery, extubation was performed in operating room. For children in conventional anesthesia group, anesthesia was given routinely and they were directly sent to ICU with a tracheal tube. Extubation time, ICU stay and hospital stay after operation were recorded. Sedation-agitation scores (SAS) were assessed and adverse reactions as well as other anesthesia -related events were recorded. Results The extubation time, ICU stay and hospital stay were significantly shorter in UFTA group (P < 0.05) and SAS at extubation was lower in UFTA group than in conventional anesthesia group, but similar in other time points. For both groups, no airway obstruction and other serious complications occurred, and incidence of other anesthesia -related events were low. Conclusions UFTA shortens extubation time, ICU stay and hospital stay for children with CHD and does not increase SAS and incidence of adverse reactions.